Some visual abilities and their relationship to the accuracy of thrusting motions in female fencers - Kalaf, Asst.L. Hind Walid; عوده, ا. م .د اشراق غالب; Kazem, Baidaa Abbas (Sulaimani Journal for Humanities, 2025)
Fencing is a sport that has garnered significant attention from specialists and athletes alike. Many consider it an exciting competitive sport that contributes to thrills and suspense through its overall capabilities, whether physical, technical, motor, or visual. This sport demands a specific harmony between visual abilities and the precision of thrusting movements. This harmony is crucial for vision and visual interaction, enhancing the accuracy of thrusts and quick reflexes, which in turn improves performance. Furthermore, analyzing the eye movements of fencers as they follow attacks reveals the impact of visual abilities on information processing and precise reaction. The coordination between vision and physical movement is vital for achieving accurate thrusts and rapid responses to the opponent's movements. This is demonstrated through developing visual abilities and training in motor response and quick reflexes, which plays a major role in improving the performance and precision of fencers, thus enhancing their performance in matches. The researchers used the descriptive method, as it was suitable for the nature of the research and the problem being addressed. The sample consisted of ten female fencers from the College of Physical Education and Sports Sciences for the épée discipline during the 2024-2025 sports season. The results showed a strong correlation between visual ability, motor accuracy, and the accuracy of the thrusting motion. Fencers with a high ability to track moving objects were able to achieve more accurate thrusts. There was a clear impact of hand-eye coordination on reaction speed and thrusting accuracy, indicating the importance of developing this skill through specialized training. Visual abilities play a pivotal role in improving anticipation and rapid response, which positively impacted the athletes' performance. Fencers with high levels of visual ability demonstrated superior decision-making speed during matches, indicating the need to enhance these abilities within training programs. The recommendations included: incorporating specialized training to improve visual-motor ability, such as tracking moving targets using visual simulation software; and developing hand-eye coordination exercises using rapid reaction drills and activities that require precise responses. Visual tracking is enhanced through exercises that involve identifying and responding to moving targets within specific timeframes. Modern technologies, such as virtual reality programs, are also utilized to develop visual interaction and improve the speed of response among female athletes. Further studies are needed to understand the impact of other cognitive factors, such as visual attention and anticipation, on skill performance in fencing.
Keywords: Visual abilities; precision of thrusting motion; fencing sword weapon